2021
DOI: 10.3390/plants10101980
|View full text |Cite
|
Sign up to set email alerts
|

Plastome Characterization and Phylogenomic Analysis Yield New Insights into the Evolutionary Relationships among the Species of the Subgenus Bryocles (Hosta; Asparagaceae) in East Asia

Abstract: The genus Hosta, which has a native distribution in temperate East Asia and a number of species ranging from 23 to 40, represents a taxonomically important and ornamentally popular plant. Despite its taxonomic and horticultural importance, the genus Hosta has remained taxonomically challenging owing to insufficient diagnostic features, continuous morphological variation, and the process of hybridization and introgression, making species circumscription and phylogenetic inference difficult. In this study, we se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…In addition, it has relatively high genetic variation; therefore, it is often employed to infer the genetic relationships of species, estimate their differentiation time [12][13][14][15], and sometimes identify germplasm [16]. For example, Zeb et al compared the cp genomes of twenty-four Pinus species and identified a total of thirteen divergent hotspot regions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has relatively high genetic variation; therefore, it is often employed to infer the genetic relationships of species, estimate their differentiation time [12][13][14][15], and sometimes identify germplasm [16]. For example, Zeb et al compared the cp genomes of twenty-four Pinus species and identified a total of thirteen divergent hotspot regions.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast genome sequences are commonly used in various areas of biology, i.e., phylogenetics [37,38], DNA barcoding [39,40], taxonomy, evolution, and population genetics [41] of both angiosperms and gymnosperms. In the last five years, many genomic studies of various representatives of the genus Dracaena [25,26] and the family Asparagaceae [22,23,42,43] have also been published, but so far, none have included D. cinnabari. Taking into account the lack of genomic study on this iconic species, we decided to provide new and valuable omics data which enable the protection of its genetic resources as well as for further phylogenetic studies of the genus Dracaena.…”
Section: Discussionmentioning
confidence: 99%
“…We also found no major differences in the number of annotated genes in D. cinnabari and other Dracaena species. The complete chloroplast genome of D. cinnabari has a typical quadripartite structure, consisting of a pair of inverted repeats (IRs), separated by a large single-copy region (LSC) and a small single-copy region (SSC) that occurs in many other plant species [45][46][47], including those of the genus Dracaena [25,26] and the family Asparagaceae [23,24,42,43]. Our findings in this study regarding the organization of the D. cinnabari cp genome are very similar to those previously published for other members of the genus Dracaena [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The pairwise sequence divergence was calculated based on the Kimura 2-parameter method ( Kimura, 1980 ) using MEGA11 ( Tamura et al., 2021 ). According to earlier studies, we sequenced the entire plastome (e.g., Kim et al., 2019 ; Cho et al., 2020 ; Yang et al., 2021 ; Yun and Kim, 2022 ). An Illumina paired-end (PE) genomic library was constructed and sequenced using the Illumina HiSeq platform (Illumina, Inc., San Diego, CA, USA) at Macrogen Corporation (Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, as of today, we have very limited phylogenetic relationships among Phedimus species in East Asia, and phylogenomic analysis based on the complete plastome using broader sampling has never been conducted to gain insight into the origin of Korean endemic species. Plastome-based phylogenomic analysis has provided good resolutions and supports, demonstrating its importance in various plant groups (e.g., Xie et al., 2019 ; Cho et al., 2020 ; Xie et al., 2020 ; Yang et al., 2020 ; Yang et al., 2021 ). Since the plastome represents the evolutionary history of maternal lineages only, we employed nrDNA ITS sequences to complement the phylogenetic inferences from the plastome sequences.…”
Section: Introductionmentioning
confidence: 99%